Study of the Main Dimensions of Fiberglass Fishing Boats in the Waters of South Buton Regency - Azhar Aras Mubarak; Samaluddin; Alfiah Alif (Edelweiss : Journal Of Innovation In Educational Research, 2023)
Availability of vessel design and capacity according to the wishes of fishermen groups on a small scale,especially in the area of South Buton Regency must be carried out. Taking into account the cost of makingships and the use of fiberglass materials, it is hoped that a ship design will be produced that is for accordancewith the wishes of the community. The main ship size study provides many options in choosing ships withdifferent characteristics but having almost the same ship volume. This study aims to identify and compareseveral main ship sizes that are designed and provide choices according to existing requirements. The resultsshowed that with a ship length of 7 m, width of 1.5 m, and of 0.72 m, the ship would have a resistance of 2.8kN, a power of 14.22 kW and a displacement of 1464 kg and a surface area of 226854.22 cm2. Meanwhile,with a ship length of 7.25 m, width of 1.5 m, and of 0.70 m, it will have a resistance of 2.9 kN, a power of 14.7kW and a displacement of 1474 kg and a surface area of 232578.12 cm2. Whereas with a ship length of 7.50 m,width of 1.5 m, and of 0.68 m it will have a resistance of 1.6 kN, a power of 15.22 kW and a displacement of1481 kg and a surface area of 238195.85 cm2.